1989
DOI: 10.1152/jappl.1989.66.5.2196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of undernutrition on diaphragm fiber size, SDH activity, and fatigue resistance

Abstract: The influence of prolonged nutritional deprivation on the succinate dehydrogenase (SDH) activity and cross-sectional areas of individual fibers in the rat diaphragm and deep portion of the medial gastrocnemius (MGr) muscles was determined. Fatigue resistance of the diaphragm was measured by means of an in vitro nerve-muscle strip preparation. Fiber SDH activity and cross-sectional area were quantified by means of an image processing system. Diaphragm fatigue resistance was significantly improved in the nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
97
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 0 publications
12
97
2
Order By: Relevance
“…COPD patients use accessory breathing muscles almost constantly to breathe, and this may cause such a training effect. In animal studies, malnutrition has shown a relative increase of type I fibres [27,28]. Since, in this study, the COPD patients suffered from tissue depletion compared to the healthy subjects, differences in fibre composition may have been a contributing factor to an earlier metabolic adaptation in the patients.…”
Section: Discussionmentioning
confidence: 67%
“…COPD patients use accessory breathing muscles almost constantly to breathe, and this may cause such a training effect. In animal studies, malnutrition has shown a relative increase of type I fibres [27,28]. Since, in this study, the COPD patients suffered from tissue depletion compared to the healthy subjects, differences in fibre composition may have been a contributing factor to an earlier metabolic adaptation in the patients.…”
Section: Discussionmentioning
confidence: 67%
“…Muscle fibers with a mainly oxidative met abolic pathway are relatively resistant to ND-induced catabolism (28,30). This may explain why, in the pres ent study, ND affected type I and Ha fibers less than type lib fibers.…”
Section: Discussionmentioning
confidence: 82%
“…This degree of wasting on it s e lf , e.g., induced by nutritional depletion (ND), may c a u s e structural changes in the DIA, accompanied by abnorm alities in contractile properties (14,15,18,30). T h e s e studies, however, were discrepant with regard to t h e fiber types affected.…”
mentioning
confidence: 99%
“…The possible role of malnutrition is demonstrated by animal studies in which nutritional deprivation caused depressed muscular mitochondrial capacity [33][34][35]. Physical inactivity or disuse of limb muscles are potential contributors to the observed fibre-type shift [36].…”
Section: Discussionmentioning
confidence: 99%